2019
DOI: 10.1186/s13244-019-0792-9
|View full text |Cite
|
Sign up to set email alerts
|

Gender discrepancy in research activities during radiology residency

Abstract: ObjectiveTo investigate the presence of gender disparity in academic involvement during radiology residency and to identify and characterize any gender differences in perceived barriers for conducting research.MethodsAn international call for participation in an online survey was promoted via social media and through multiple international and national radiological societies. A 35-question survey invited radiology trainees worldwide to answer questions regarding exposure and barriers to academic radiology duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
(28 reference statements)
0
17
1
Order By: Relevance
“…All included articles were written in English and published between 1989 and 2020 [ 6 , 7 , 11 , 12 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , <...>…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All included articles were written in English and published between 1989 and 2020 [ 6 , 7 , 11 , 12 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , <...>…”
Section: Resultsmentioning
confidence: 99%
“…Five articles were published in Canada [ 86 , 98 , 99 , 111 , 126 ] and two in France [ 76 , 109 ]. One article was an international multicenter study [ 118 ], and two resulted from a collaboration between Australia and Ireland [ 89 ] and Vietnam and Malaysia [ 12 ], respectively. One article each was published in Italy [ 101 ], Switzerland [ 78 ], Saudi Arabia [ 72 ], the United Kingdom [ 120 ], and South Korea [ 125 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, data published in 2014 indicated that at American medical schools, women represented only 21% of full professors and 16% of deans [9], and currently, among the 428 department heads in the European Society of Radiology database, only 20.6% are women. As academic success tends to be linked to advancement to leadership positions, closing this gap will require, among other steps, consciously encouraging women's participation in research, which already lags behind men's at the residency stage [10].…”
Section: Women In Focusmentioning
confidence: 99%